UMA EPOP?IA DE INDIGNA??O E TERNURA Meu querido canibal sob a ?tica da metafic??o historiogr?fica - Souza, Eug?nia Mateus de (2007)
After reading Meu querido canibal (My dear Cannibal) by Antonio Torres, this dissertation searches to map the colonial imaginary in the contemporary era by re-revisiting the history with a postcolonial view. The crystallization is broken by the metafictional paradox in order to allow the fitting of one more piece of the mosaic that forms the Brazilian cultural nation/ identity. The myth of nation, as founder of a community, generated a large number of possible and varied researches and inventions. Torres uses myths and shows the narrative of a colorless nation, to recognize in its identity the hybrid generated not only by the process of acculturation, but something more specific related to the process of transculturation. Several people from different territories settled down to the same area, creating a history of cultural diversity. Literature is responsible for recovering past/present, inside/outside in acts of anthropophagy to express the national culture. The mapping of the colonial imaginary enlarges a universe inside the singularities that do not permit boundaries, because they are made by man who resists on recognizing himself in another one. Meu querido canibal represents this conflict in recognizing the other: the Brazilian Indian tribes used to live in war; however, the fight against the invaders joined the Indians of the tribes by to the Great Indian Chef Cunhambebe, in Confedera??o dos Tamoios (Tamoio Confederation). The Tamoio tribe lost its area; they were away from it, trying to reconquer its land. Facing the European settlers, who didn t consider an uncivilized Indian culture with lack of organization, was a tough task. A different way of looking allows an understanding of the hybridism in the formation of a collective and plural identity. Hybridism in all senses: race, language, culture In this sense the subordinate space appears: the interstice , the nowhere. A space formed by the undeniable process of transculturation, that formed the builder Brazilian people creator that has also created the image of the fissures of diversity, located in a space that does not recognize the borders that feature a past load of denial, superiority, and exploration. The contemporary anthropophagy is reanalyzed by Torres through the fiction, repeating from another place and with another view, the history of the cultural dominance.